ANALYSIS OF THE DYNAMICS OF REFRACTION DISORDERS IN SCHOOLCHILDREN TROUGHOUT THE YEAR - Plyska, O.I.; Kharchenko, L.B.; Grusha, M.M.; Lazoryshynets, V.V.; Shkrobanets, I.D. (World of Medicine and Biology, 2020)
The article used a retrospective analysis to investigate the state of the visual system of students of different ages and genders. For this purpose, refractive errors (myopia, hyperopia, astigmatism and myopia or hyperopia with astigmatism) and contrast sensitivity in the dynamics of the year were determined. There was an incredible increase in refractive errors (from 60.12 % to 65.32 %): myopia (from 33.53 % to 36.88 %) and hyperopia (from 20.23 % to 21.97 %). The study of contrast sensitivity revealed its reduction from 2.5 (limit value) to 2.0 in 10.15 % of cases. The use of corrective means prevented the progression of refractive errors. At the same time, their non-use is accompanied by the progression of refractive errors in 97.67 %. It was found that the limit value of the contrast sensitivity index =2.5 is important for further prediction of changes in the visual system of schoolchildren and can be used for preclinical rapid diagnosis of visual impairment. Students with contrast sensitivity 2.5 are at risk and need careful monitoring of their refractive apparatus for a long time, which allow us to detect refractive errors of the visual analyzer in the early stages and to apply corrective means in a timely manner.